SENSES OF GESTURAL LANGUAGE: GESTURAL TRANSPOSITION AND REPRESENTATION - de Barros, Diana Luz Pessoa (Laboratório Editorial FCL-UNESP, 2011)
The aim of this article is to present, from the French Discursive-Semiotics approach, some theoretical directions to the study of the senses of gesture in the contemporary society in four circumstances: the poetical gesture of the dance; the gesture in physiotherapy treatment; the passage from the gesture to the “sign’ in the sign language; gesture represented in painting, photography, publicity, etc. The main focus of this study begins with the Greimas´s study Conditions d’une sémiotique du monde naturel (1970, p.62). From this theoretical outline, we deal with two questions: the operations in gestural transposition – semantization, desemantization, imitation, symbolization, passage from gesture to sign, in sign languages; the representation in gesture language, particularly in bank advertising, and the effects of senses produced in such advertising speeches.